Relations of Global Power : Neoliberal Order and Disorder - Teeple, Gary, 1945-; McBride, Stephen (Book collections on Project MUSE., 2014)
1. Financialization and Neo-Liberalism / David M. Kotz -- 2. The New Constitutionalism: International and Private Rule in the New Global Order / Stephen McBride -- 3. The Privatization of Authority in the Global Political Economy / Claire Cutler -- 4. Corporate Accountability: Is Self-Regulation the Answer? / Kavaljit Singh -- 5. Globalizing the Labour Process / Bob Russell -- 6. Regulating Labour Standards in the Global Economy: Emerging Approaches to Global Governance / Mark Thomas -- 7. Global Health: A Political Economy of Historical Trends and Contemporary Inequalities / David Coburn -- 8. Castles in the Air: "Universal" Human Rights in the Global Political Economy / Tony Evans -- 9. Military Power, Hegemonic Power: A Neglected Issue of International Political Economy / James Cypher -- 10. Resisting Neo-Liberal Capitalism: Insights From Political Economy / Elaine Coburn